The The new CAP and the challenge of sustainability: a synthetic indicator for the Italian wine sector - Roberta Sardone; Simonetta De Leo; Davide Longhitano; Roberto Henke (Wine Economics and Policy)
Among the keys enabling the actors of the food chain to become more sustainable, the Strategy assigns an important role to knowledge and information. For this reason, the Farm to Fork Strategy aims to make the Farm Accountancy Data Network (FADN) the main data source of sustainable indicators, turning it into a Farm Sustainability Data Network (FSDN). Wine not only represents one of the most important products of the Italian agri-food system (value of turnover and exports), but it is also characterised by a widespread use of traditional certification systems (PDO/PGI, Organic), to which in recent years specific certifications of sustainability have been added, evaluated through its threefold dimension: economic, environmental, and social. Indeed, wine is much ahead of other sectors in the process of sustainability certification both for the process and the product itself. The paper is an effort to test the current set of information included in the FADN and some related computable indicators as a feasible tool for the assessment of sustainability in the wine sector. The goal of this paper is twofold. Firstly, we assess the actual level of sustainability of the wine sector in Italy through an indicator that synthetizes the three dimensions (economic, environmental, and social) of sustainability at the regional level. Secondly, more in general, we test the current capacity of the FADN information to provide a reliable measure of sustainability given the intention of the EU legislator to switch the European data network from FADN to FSDN.